New results in impulse-free continuous-time cheap LQ optimal control - Ferrante, A.; Ntogramatzidis, Lorenzo (IEEE, 2014)
In this paper, we provide conditions for the solvability of LQ (linear-quadratic) optimal control problems in which the input function is not penalised in the performance index. In particular, we focus our attention on regular input functions, i.e., on the control functions that do not involvedistributions, which in general appear in the solution of singular problems.